2022
DOI: 10.1016/j.ajo.2021.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biometric Features and Their Association With Axial Length in High Myopia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Corneal curvature radius was significantly larger in HM eyes, as previously reported. 22 Intra-visit reproducibilities of the angiography scans were 0.908 and 0.964 for global cpVD of eyes with and without HM, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Corneal curvature radius was significantly larger in HM eyes, as previously reported. 22 Intra-visit reproducibilities of the angiography scans were 0.908 and 0.964 for global cpVD of eyes with and without HM, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The evaluation of the relationship between AL and WTW distance with CV in the present study indicated that these parameters were significantly inversely related to CV. A look at previous studies shows that the longer the AL, as seen in high myopic patients, the lower the CV 13 ; one of the possible reasons may be the lower corneal thickness in individuals with longer AL. 14 As the AL increases, the sclera becomes more elongated and thinner; the corneal stroma is also stretched similarly and the CV decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients seeking ophthalmological consultation, aged 18 years or older, were consecutively recruited. Participants with (1) history of an ocular surface and/or intraocular surgery or procedure; (2) presence of any ocular or systemic disease affecting the ocular surface, including eyelid pathology, corneal ectasias and dystrophies, Sjögren syndrome, or diabetes mellitus, among others; (3) prior or current history of allergic diseases potentially leading to eye rubbing (i.e., atopy, eczema, conjunctivitis); (4) history of contact lens wear; (5) high myopia (spherical equivalent < − 6.00 diopters) 12 ; and (6) ocular hypertension or glaucoma were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…(3) prior or current history of allergic diseases potentially leading to eye rubbing (i.e., atopy, eczema, conjunctivitis); (4) history of contact lens wear; (5) high myopia (spherical equivalent < − 6.00 diopters) [12]; and (6) ocular hypertension or glaucoma were excluded.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%